The comparison of Mental Index based on dental status in women using panoramic radiographs - Therine Arnecia; Intan Farizka; Sariyani Pancasari Audry Arifin (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2023)
Background: Bones will experience a decrease in density due to an imbalance in the process of resorption and remodeling. Women are known to be at greater risk of bone density loss than men, due to aging and hormonal effects. Decreased bone density can also affect alveolar bone and attachment to teeth, leading to tooth loss and edentulous. Panoramic radiographs are one of the regular examinations at dental clinics. They observe changes in the thickness of the cortical bone of the mandible and detect abnormalities in bone density by measuring them using the Mental Index (MI). Objectives: This research is aimed to determine the differences in Mental Index (MI) between dentate and edentulous regions in women through panoramic radiographs. Materials and Methods: This research is using comparative analytic observational study with a cross-sectional approach, with 160 women panoramic radiograph samples available at the Dentistry Radiology Installation, RSGM-P, Trisakti University FKG, divided between 80 samples of the dentate region and 80 samples of the edentulous region. Calculations using MI with i-Dixel software version 2.2.0.3. (Morita, Japan) results in millimeters. Results: There is a significant difference of MI between dentate and edentulous region (p = 0.000). The mean of dentate MI (right region 3.7443 ± 0.47927 mm and left region 3.7373 ± 0.41075 mm) was greater than edentulous MI (right region 2.4725 ± 0.48391 mm and left region 2.4421 ± 0.43962 mm). Conclusion: The loss of teeth in women may lead to any change in the Mental Index (MI) Keywords: Bone Density; Dental Status; Mental Index; Panoramic Radiograph